1996
DOI: 10.1002/(sici)1097-4628(19961212)62:11<1847::aid-app9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

On the selectivity of adsorption chromatography

Abstract: SYNOPSISIn this paper, the shape of chromatograms obtained by elution of copolymers with a mixture of solvent-nonsolvent of variable composition has been studied from a theoretical point of view. It is assumed that the thermodynamic quality of the mixture a t which the copolymer is eluted depends only on its composition and not on its mass and structure. If one characterizes the polydispersity in composition, assuming that each constituent obeys a molar mass distribution of the Zimm-Schulz type, one can draw t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The detection was performed using a UV detector (Waters 481) and an evaporative light scattering detector (DEDL 21, Eurosep). Details on the experimental conditions can be found in ref b.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection was performed using a UV detector (Waters 481) and an evaporative light scattering detector (DEDL 21, Eurosep). Details on the experimental conditions can be found in ref b.…”
Section: Referencesmentioning
confidence: 99%
“…The linear increase in M n after styrene addition, the complete shift of the SEC traces (both refractive index and UV traces), and the decrease in the M w / M n to 1.27 clearly indicated that chain extension was effective. Furthermore, liquid adsorption chromatography (LAC) 25 (Figure ), which performs separation according to the chemical composition, did not show any detectable poly( n -butyl acrylate) homopolymer, signifying efficient reinitiation by the first block. A different result was found when styrene was polymerized first; in particular, reinitiation was incomplete, even at high conversion in the second step, as demonstrated by the SEC and LAC analyses.…”
mentioning
confidence: 99%